LITERATURE REVIEW: AKTIVITAS ANTIBAKTERI EKSTRAK DAUN RAMANIA (Bouea macrophylla Griffith) - Tulak Rerung, Lola' (Politeknik Tiara Bunda, 2024)
The ramania plant (Bouea macrophylla Griffith) is still very limited in its use, however ramania leaves have the potential to control the wound healing process or infection. Infections are generally caused by bacteria such as Staphyloccous aures, Escherichia coli, Actinomyces spp, and many more. This literature review research aims to determine the antibacterial activity of ramania leaf extract (Bouea macrophylla Griffith). The method used in the review process for this article is a narrative review through searching articles that have been published both nationally and internationally. Searching research journal libraries, scientific articles and journal reviews via Google Schoolar, Researchgate, and the Garuda Portal. This literature review study was obtained from article searches. research in the last 10 years. There are 5 journals that meet the specified inclusion and exclusion criteria. Based on the results of the literature review that has been carried out, it was found that ramania/gandaria leaves have potential as an antibacterial treatment. The antibacterial activity in ramania leaves is due to the work activity of the secondary metabolite compounds contained therein, including alkaloids, flavonoids, saponins, steroids, quinones and tannins. Ramania leaves have moderate to strong activity against the bacteria Staphylococcus aureus and Actinomyces spp, while the antibacterial activity of ramania leaves is weak against Escherichia coli.